The Effects of Chronic Exposure to Airport Related Noise on Blood Pressure (A Case Study of area nearby Ahmad Yani International Airport, Semarang) - Afnita, Hani; Poerwito S., Poerwito S.; Muhtarom, Muhtarom (Fakultas Kedokteran; Universitas Islam Sultan Agung (UNISSULA), 2013)
The chronic exposure of airport related noise can lead to decreased quality of health and is a risk faktor of disease. Noise can stimulate physiological response to cardiovascular parameters such as blood pressure. The increase in blood pressure can be used as indicator of disturbance of the cardiovascular system. Ahmad Yani Airport is an international airport with a high mobility, thus people living near, are susceptible and have a risk for decreased quality health. Thus, the purposes of this study was to determine the effects of chronic noise exposure of airport related noise on the blood pressure. The study was an observational analytic cross-sectional study. This research was conducted in the area near Ahmad Yani Airport in Semarang, which is located on Perumahan Cakarawala (Â± 1000m) and Perumahan Semarang Indah (Â± 5000m). Total of 60 respondents were randomly included in the study. Noise is measured with a Sound Level Meter (SLM) Extech Type 70 335 with Leq measurement method (Equivalent Continous Noise Level) for 24 hours (Lsm). The preliminary questionnaire was distributed to fulfill the criteria of inclusion and exclusion. The blood pressures were evaluated using the mercury Spygmomanometer, before and after exposure (flight activity). Data were analyzed with dependent t test. Noise measurements indicated that the Perumahan Cakrawala II had ahigh noise exposure above the noise level standards (NAB) of 69 dBA (Lsm > NAB 55dBA), while the Perumahan Semarang Indah has noise exposure at 51 dBA below the NAB. The results indicated that the chronic noise exposure of flight activity had significant effect on blood pressure (p = 0.00). The increase in blood pressure among Perumahan Cakrawala II respondents was higher (systolic: by 83.3%), diastolic: by 59.9%) compared to Perumahan Semarang Indah (systolic: by 69.9%, diastolic : by 49,9%). In conclusion, exposure to chronic noise due to flight activity significantly affected blood pressure.